Harnessing the Power of Honey: A Natural Antioxidant for Enhancing Aseel Sperm Motility During Preservation - Miah, Abdul Gaffar; Pramanik, Md. Ahsan Habib; Mehta, Basant Kumar; Salma, Ummay (International Journal of Applied Sciences and Biotechnology, 2025)
Semen cryopreservation is essential for poultry breeding, preserving genetic diversity, and the advancement of artificial insemination techniques. However, oxidative stress remains a major limitation during semen storage, as it negatively affects sperm motility, structural integrity, and fertilizing ability. This study investigated the potential of honey, a natural antioxidant-rich substance, in improving sperm motility of Aseel roosters during short-term storage. Semen was collected from sixteen healthy and mature Aseel roosters and diluted using modified Ringer’s solution supplemented with varying concentrations of honey (1%, 2%, 3%, 4%, and 5%). A control group without honey supplementation was maintained for comparison. Semen quality parameters, including sperm concentration, total motility, progressive motility, non-progressive motility, and percentage of immotile sperm, were evaluated at 0, 2, and 4 hours post-storage using a Computer-Assisted Semen Analyzer (CASA). The results indicated that honey significantly (P<0.05) enhanced sperm motility, with the 3% honey group showing the highest total motility (87.80%) at 2 hours of storage, compared to the control (66.23%). The improvement in motility is attributed to the antioxidant compounds in honey, particularly flavonoids and polyphenols, which help reduce lipid peroxidation and preserve cellular function. These findings demonstrate that a 3% concentration of honey is optimal for maintaining sperm motility during short-term preservation. The use of honey as a natural and non-toxic additive in semen extenders offers a promising alternative to synthetic compounds. Incorporating honey into semen preservation protocols may enhance reproductive efficiency and support the sustainable conservation of indigenous poultry breeds like the Aseel. Int. J. Appl. Sci. Biotechnol. Vol 13(2): 81-86.